1990
DOI: 10.1523/jneurosci.10-03-00909.1990
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of experience-dependent synaptic modifications in striate cortex by infusion of an NMDA receptor antagonist

Abstract: To assess the possibility that NMDA receptors play a special role in visual cortical plasticity, the selective antagonist 2-amino-5- phosphonovaleric acid (APV) was continuously infused into the striate cortex of kittens as the visual environment was manipulated during the critical period. The cortex was studied using single-unit recording from sites between 3 and 6 mm from the infusion cannulae. One week of D,L-APV infusion coincident with monocular deprivation or “reverse suture” produced a concentration-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
248
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(261 citation statements)
references
References 56 publications
11
248
2
Order By: Relevance
“…Our results in the ferret LGN contrast with studies of cat visual cortex, in which ocular dominance plasticity requires NMDA receptor activation (Bear et al, 1990) but does not seem to require NO (Gillespie et al, 1993;Daw et al, 1994). Consistent with this difference, NADPH-diaphorase staining is developmentally regulated in LGN neurons but not in visual cortical neurons.…”
Section: Discussioncontrasting
confidence: 94%
“…Our results in the ferret LGN contrast with studies of cat visual cortex, in which ocular dominance plasticity requires NMDA receptor activation (Bear et al, 1990) but does not seem to require NO (Gillespie et al, 1993;Daw et al, 1994). Consistent with this difference, NADPH-diaphorase staining is developmentally regulated in LGN neurons but not in visual cortical neurons.…”
Section: Discussioncontrasting
confidence: 94%
“…Indeed, enrichment in the adult causes changes in the NMDA receptor expression and in the expression of downstream molecules (Rampon et al, 2000;Molteni et al, 2002). NMDA receptors have been demonstrated to play a crucial role in ocular dominance plasticity and in development of receptive field properties in the visual cortex (Bear et al, 1990;Roberts et al, 1998;Ramoa et al, 2001;Fagiolini et al, 2003) and to be highly sensitive to activity (Quinlan et al, 1999;Philpot et al, 2001). Interestingly, Liu et al (2000) have shown that maternal care affects NMDAR subunit expression in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…172 NMDA receptor blockade impairs induction of long-term potentiation (LTP) which is important for memory formation. 173 In addition, MK-801 causes acute but reversible neuronal vacuolization when systemically administered at neuroprotective doses in adult rodents. 174 Even more concerning, in the developing brain NMDA antagonists such as MK-801 have long lasting effects on neuronal circuits, 175 can trigger widespread apoptotic neurodegeneration in the developing brain 176 and indeed while MK-801 after head injury protected against primary necrotic damage it actually increased severity of secondary apoptotic damage.…”
Section: With What Should Cooling Be Given?mentioning
confidence: 99%